APAKAH KEPRIBADIAN ANDA MEMPENGARUHI ANDA DALAM BERBELANJA? MENGKAJI HEDONIC DAN UTILITARIAN SHOPPING VALUE DARI SUDUT PANDANG BIG-FIVE PERSONALITY - Alhad, Muhammad Afif (Universitas Sahid Surakarta, 2021)
Shopping has been part of individual’s daily life. There are several types of individual in terms of shopping and factors responsible for those types. This study investigated the role of big-five personality trait (neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness) toward hedonic shopping value and utilitarian shopping value. This study applied quantitative approach. This study consisted of 330 respondents with the minimum age of 18 attained from accidental sampling. Research instrument used in this study was big-five inventory for measuring personality trait, while for measuring shopping value researcher used scale of hedonic and utilitarian shopping value. Results from multiple linear regression analysis indicated that extraversion personality trait and neuroticism personality trait had significant positive role in hedonic shopping value. Conscientiousness personality trait had significant positive role in utilitarian shopping value, while neuroticim personality trait had significant negative role in utilitarian shopping value. Practical implication of this study were related to marketing strategy based on consumer’s personality profile.